The Ma'ālim al-Qurba fī ahkām al-hisba of Diya' al-Dīn Muhammad ibn Muhammad al-Qurashī al-Shāfii̇̄, knownas Ibn al-Ukhuwwa - Ibn al-Ukhūwah, Muḥammad ibn Muḥammad, 1250 or 1251-1329. (London)
XVII+113+246 s.